Strategic plan for Davao Doctors Oncology Center Inc. - Sotana, Demosthenes V.; Digal, Larry N.; Concepcion, Sylvia B.; Gomez, Aurelia Luzviminda V. (Davao City School of Management, University of the Philippines Mindanao, 2008)
Radiotheraphy is one of the most popular treatment modalities for cancer cases. And Cancer is the third highest cause of morbidity and mortality in the Philippines and all over the world. The only other diseases that posted greater number in the WHO census are cardiovascular diseases and Heart problems. The probability of having cancer increases with age and it is estimated that about one in every 1800 of the population will develop cancer yearly. This could be translated to about 637 new cancer cases for Davao City alone and about 2,888 new cases for the region. It could be be used alone or in combination with other treatment regimens. At a growth rate of about 2.8 percent it is estimated that the population will double in the year fourteen to fifteen years. Cancer as a disease itself is registering an increase and in the last 30 years, according to her lecture, ?the incidence of cancer has increased 26% in 65 year-old population as compared with a 10% increase in the population 65 years. ?Browner I., 2005). Davao Doctors Oncology Center Incorporated is uniquely positioned as the only radio-therapy provider for located in the Davao region. However in the eight years of its operations, the average patient enrollment is only about 289 patients per year out of this number about 93 percent of its patients come from within Davao City. This paper attempts to identify critical factors that have preventive DDOCI from attaining its Vision and Mission in serving the radiotherapy requirements of the people of Mindanao. The model of J.A. Pears and R.B. Robinson was employed in and the SWOT analysis was used in formulating strategic options to help the corporation attain its goals.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2008.
Keywords: Strategic plan